A Changing Pattern of Suicide Mode in Sri Lanka - Niwantha, Haputhanthrige Pathum; Ekanayake, EMS; Siriwardhane, W.S.N; Wickramage, P.D (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 2 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2024)
We can identify suicide as a social problem that has emerged strongly in Asian society. Suicide is simply taking one's natural life voluntarily. Although there is a long history of suicide socially and culturally, with the development of modern social pattern and human civilization, suicide has been defined as a regressive act in the society. Similarly, the main objective of this study is to study whether there has been a change in suicide tactics in Sri Lanka due to the modernization process, whether there has been a change in suicide compared to the population. This study has been conducted at a macro level using the entire population of suicides reported to the Sri Lanka Police from the year 2000 to 2019, and using the literature written in this regard, it was possible to identify some of the main tactics used to commit suicide. Among those tactics, drinking pesticide-related poisons, strangulation, drowning, inflicting injuries through sharp weapons and jumping on trains can be identified as the main tactics, and drinking pesticide-related poisons and strangulation are the most commonly used tactics. is possible in 2000, poisoning accounted for 37% of all suicides, and by 2012, that trend had reversed and the rate of hanging had increased slightly. As of 2013, 46% of all deaths were due to hanging, and in 2017, it has increased to 55% and 59%. It can be concluded that the trend of hanging people has intensified in modern times due to the fact that pesticide trade has been registered in a certain legal framework and hanging people have become tactically easier. But here, instead of a strong numerical change, a decrease in suicide can be identified. In order to control this degenerate situation, the main factors affecting it should be identified and those reasons should be regulated. It can be recognized that individual mental health imbalance, family background and economic weakness are the main causes, and therefore, to manage those conditions, individual personality development projects should be developed. Also, in order to control the economic and social anomie, the state should be implemented to prepare an environment suitable for living, and approaches such as crime prevention should be used through environmental and social planning.